2023
DOI: 10.3389/fphar.2023.1091858
|View full text |Cite
|
Sign up to set email alerts
|

Differences in bioavailability and cognitive-enhancing activity exerted by different crystal polymorphs of latrepirdine (Dimebon®)

Abstract: Introduction: Pharmacokinetic characteristics as well as cognitive-enhancing nootropic activity of latrepirdine (Dimebon®) in relationship with its polymorphic forms have been studied in SD and Wistar rats.Methods: The pharmacokinetics of six polymorphs (A, B, C, D, E, F) of latrepirdine were studied in male SD rats after 7 days of oral administration in corn oil at a dose of 10 mg/kg once a day. Blood and brain samples were taken on the 7th day of administration at 15 min, 30 min, 60 min and 120 min after adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…51 Studies have shown that patients with cognitive impairment exhibit low levels of NA C24:1 ω-9, and nutritional supplementation with NA C24:1 ω-9 is thought to enhance cognitive function and brain development. 37,52 Our previous study revealed that ASO supplementation can regulate FAs and improve cognitive function in healthy rats. We propose that the synergistic effect of NA with essential FAs induced by ASO supplementation contribute to the improvement of cognitive performance in HIE rats.…”
Section: Papermentioning
confidence: 99%
“…51 Studies have shown that patients with cognitive impairment exhibit low levels of NA C24:1 ω-9, and nutritional supplementation with NA C24:1 ω-9 is thought to enhance cognitive function and brain development. 37,52 Our previous study revealed that ASO supplementation can regulate FAs and improve cognitive function in healthy rats. We propose that the synergistic effect of NA with essential FAs induced by ASO supplementation contribute to the improvement of cognitive performance in HIE rats.…”
Section: Papermentioning
confidence: 99%
“…33 The pharmacokinetics and cognitive-enhancing nootropic activity of the drug latrepirdine (Dimebon), that exists in 6 polymorphic forms, demonstrated that only one of the latrepirdine polymorphs showed significant nootropic activity, while five other patentprotected polymorphs did not provide any statistically significant therapeutic effect. 48 Difficulties in characterization and differentiation of five polymorphic forms resulted in the drug cefdinir, originally patented in both Japan and the US, 49−51 being simultaneously patent-protected by as many as 11 patents. 52 Unfortunately, the existence of polymorphs is impossible to predict based on a compound's structure.…”
Section: Polymorph Formationmentioning
confidence: 99%
“…For example, several clinical failures were reported for carbamazepine due to different polymorphs of the branded and generic drug, , and for which crystal engineering studies found as many as 13 new crystalline phases . The pharmacokinetics and cognitive-enhancing nootropic activity of the drug latrepirdine (Dimebon), that exists in 6 polymorphic forms, demonstrated that only one of the latrepirdine polymorphs showed significant nootropic activity, while five other patent-protected polymorphs did not provide any statistically significant therapeutic effect . Difficulties in characterization and differentiation of five polymorphic forms resulted in the drug cefdinir, originally patented in both Japan and the US, being simultaneously patent-protected by as many as 11 patents …”
Section: Problems With Conventional Solid-state Drugsmentioning
confidence: 99%